Silicon carbide based inverters for energy efficiency - Vu, P. L. A. (2013)
The device characteristics for the normally off SiC JFET are superior to MOSFETs and IGBTs and offer the possibility of efficiency improvements from reduced conduction and switching losses. The work presented in this paper gives an assessment of the silicon carbide power modules in power inverters. Output characteristics and switching energy loss characteristics based on experimental data are incorporated. Comparison of total power losses and efficiency of a silicon carbide based three phase inverter with silicon base is analyzed and studied. The efficiency of the silicon carbide based inverters based on chosen device is found to be above 99%, and more efficient than most conventional silicon based IGBT inverters. This is most so at high switching frequency.